(untitled) (Perner’s Contacts, 2017)
The article deals with the deceleration threshold placed on the road and its impact on road car. There is a software modeling a car crossing over the cross threshold. The aim of this paper is to determine the transmission of forces into a road vehicle body. And when crossing uneven terrain at different speeds.